SOIL MERCURY SURVEY AT MAKAROYEN VILLAGE IN KOTAMOBAGU GEOTHERMAL FIELD, NORTH SULAWESI, INDONESIA - Riogilang, Hendra (JURNAL ILMIAH MEDIA ENGINEERING, 2016)
Kotamobagu geothermal field is one of the prospectiveÂ  geothermal development in North Sulawesi, Indonesia. The soil mercury survey were conducted in Kotamobagu, mainly withinMakaroyen village, on the foot of Ambang Mountain. Concentrations of soil mercury (soil Hg), were measured for 20 sampling points in the area of 1.0 km EW and 1.0 km NW with elevation around 1000 m above sea level. High concentrations of soil mercury, 2920 to 17900 ng/g soil, were mainly measured in the northeast and east of the study area whereas lower concentrations to the centre, south and to the west. High concentration of soil mercury 14900 ng/g soil and above it was detected in the northeast and east of the area Makaroyen village. The presence of flow path of high temperature fluid and heat source is expected below the areas with high concentrations of soil mercury. Â Keywords: Kotamobagu, Survey, Potency, Geothermal Field, Soil Hg